Free your 'most open' Android: a comparative discourse analysis on Android. - Mosemghvdlishvili, Lela; Jansz, Jeroen (Critical Discourse Studies, 2020)
Through this paper, we convey a comparative analysis of how Google Inc. and the Free Software Foundation Europe (FSFE) discursively construct and contest Android, a dominant mobile operating system. Methodologically, we use political discourse theory to engage in the textual analysis; identify and compare key signifiers and nodal points across the exemplary texts from the two actors, and interpret their meaning vis à vis contextual insights about the political economy of Android's production. Albeit being marketed as 'the first truly open platform' for mobiles, through our analysis we find Google's definition of open source practices strictly conditional. We argue that Google's usage of compatibility rhetorically as well as techno-legally justifies the conglomerate's control over the platform. By contrast, the discursive moment by free software activists, through a campaign 'Free Your Android' deconstructs the discourse on open source and attempts to politicize the access to code in the mobile domain. This is done by extending from the well-known developer's four freedoms onto users' privacy, due to personal character of mobile devices. Such articulation of free software in relation to privacy of user data is a new development and arguably has a potential to contribute to widening support to the movement.